Respuesta :
Answer:
None of the answer options are correct
Step-by-step explanation:
cs + rh = w
cs = w - rh
s = (w - rh)/c
The second one could be corrected by exchanging c with 1/c
The last one would be correct with judiciously applied parentheses.
The first and third have too many errors to even bother trying to correct.
answer could also be written
s = w/c - rh/c
but it is not considered reduced form.
9514 1404 393
Answer:
(d) s = (w − rh)/c
Step-by-step explanation:
Undo what is done to the variable. It is multiplied by c and rh is added to that product.
cs +rh = w . . . . . given
cs = w -rh . . . . . undo the addition of rh: add -rh to both sides
s = (w -rh)/c . . . . undo the multiplication by c: divide both sides by c
_____
Additional comment
Each entire side of the equation is divided by c. That means the entire expression (w-rh) is divided by c. It is incorrect to write that division as w-rh/c. The division bar (/) in plain text only refers to the immediately preceding and the immediately following tokens as its operands. When the expression is typeset, the division bar serves as a grouping symbol, showing you the entire numerator.
[tex]s=\dfrac{w-rh}{c}[/tex]